2010
DOI: 10.1111/j.1439-0523.2009.01683.x
|View full text |Cite
|
Sign up to set email alerts
|

Yield performances of japonica introgression lines selected for drought tolerance in a BC breeding programme

Abstract: Developing drought tolerant cultivars is a preferred strategy to solve water-shortage facing rice farmers. A backcross (BC) breeding was initiated to improve drought tolerance (DT) of japonica hybrids in North China using an elite japonica restorer, C418, as recipient and five indica cultivars as donors. A two-round-selection for yield under severe drought together with a two-round-selection for yield under irrigation resulted in 113 BC 2 F 8 introgression lines (ILs). Progeny testing allowed the identificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 18 publications
3
32
0
Order By: Relevance
“…Therefore, transgressive segregation of the rolled leaf trait in the RIL population can be partially explained by the reverse patterns of the allelic effects at the seven loci. Our results further support the observation that even though the germplasms themselves do not show prominent traits, they do harbor some excellent alleles, as previously observed for grain yield [75], salt tolerance [76], cold tolerance [13], and drought tolerance [12]. …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, transgressive segregation of the rolled leaf trait in the RIL population can be partially explained by the reverse patterns of the allelic effects at the seven loci. Our results further support the observation that even though the germplasms themselves do not show prominent traits, they do harbor some excellent alleles, as previously observed for grain yield [75], salt tolerance [76], cold tolerance [13], and drought tolerance [12]. …”
Section: Discussionsupporting
confidence: 91%
“…Unlike the extremely rolled leaf phenotype, moderately rolled leaves or leaves with various degrees of rolling, especially inside-rolled (adaxial rolled) leaves, would be a useful trait to target in breeding. Uncovering hidden diversity in the progenies of parents with minor phenotypic differences in target traits is also important for dissecting complex traits including resistance to various biotic and abiotic stresses [12, 13]. Whether the mechanisms underlying hidden diversity also function for relatively simple traits such as rolled leaves remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Overall drought tolerance of plants cannot be inferred from performance of plants under vegetative drought alone because drought stress during the reproductive stage can lead to a significant reduction in rice yield (Venuprasad et al, 2007;Centritto et al, 2009;He et al, 2010). Therefore, sustained growth and yield under drought will be the major criterion for developing drought-tolerant rice plants.…”
Section: Gudk Regulates Rice Yield By Potentially Transphosphorylatinmentioning
confidence: 99%
“…Recent studies on molecular quantitative genetics of complex traits demonstrated the fact that even though the germplasms or modern varieties do not show stress tolerance, they do harbor some excellent genes such as drought tolerance Lafitte et al 2006;He et al 2010), salt tolerance (Cheng et al 2012;Wang et al 2012), and cold tolerance (Andaya and Tai 2006;Jiang et al 2008). Such favourable genes were found to be 'hidden' in germplasms, and advance backcross populations appears to be an effective way to mine them by introgressing and further pyramiding favourable genes of parents and different donors with molecular marker technologies Guan et al 2010).…”
Section: Implications For Rice Breeding Of Dtmentioning
confidence: 99%